Pengaruh Desian Organisasional dan Locus Of Control Terhadap Perilaku Manipulatif dalam Menetapkan Harga Transfer - Kurnia Kurnia (Jurnal Akuntansi dan Auditing Indonesia, 2002)
The objective of this study is to investigate the effect of organizational design and locus of control on the manipulative behavior in transfer pricing. Using a justice theory, it was hypothesized that organizational design has a significant effect on the intensity of manipulative behavior in negotiating transfer pricing. It was also hypothesized that the manipulative behavior intensity in negotiating transfer price would be higher for individuals whose locus of control is external than that of internal.The results show that organizational design has a statisticaly significant effect on the manipulative behavior. This is consistent with the findings of prior research that studied the effect of perceptual justice on the behaviors in an organization. The results also indicate that individual variabel (locus of control) can moderate the effect of situational factor (organizational design) on the intensity of manipulative behavior in negotiated transfer price. This finding serves as important evidence about the effect of individual trait (locus of control) on the manipulative behavior in transfer pricing. This result provides important evidence about the role of organizational factors and individual trait (locus of control) in setting the policy of effective transfer pricing.Keywords: Organizational Design, Locus of Control, Manipulative Behavior, and Transfer Pricing.